Payroll Checker System Based on Employee Performance at PT GOTO Palembang Using FDD - Dona Marcelina; Indah Pratiwi Putri; Evi Yulianti (Yayasan Asmin Intelektual Berkah, 2025)
This study addresses the critical need for modernising payroll management at PT GOTO Palembang, a rapidly expanding enterprise grappling with the limitations of manual, paper-based salary processing. The research focuses on the design and implementation of a web-based Payroll Checker Information System that integrates employee performance metrics to enhance accuracy, efficiency, and transparency in remuneration processes. Employing the Feature-Driven Development (FDD) methodology, the system was developed iteratively to ensure alignment with organisational requirements and adaptability to evolving operational complexities. The system architecture encompasses modules for attendance tracking, performance evaluation, salary computation—including deductions, allowances, and meal subsidies—and comprehensive reporting functionalities. Role-based access controls were instituted to safeguard data integrity and facilitate secure access for administrators, employees, and directors. The implementation of this system has yielded significant improvements in payroll accuracy, reduced administrative workload, and enhanced employee trust through increased transparency. Furthermore, the integration of performance-based compensation aligns employee incentives with organisational objectives, fostering a culture of accountability and continuous improvement. This initiative exemplifies how strategic application of information technology can optimise human resource management practices, particularly in organisations experiencing rapid growth and structural complexity. The findings underscore the efficacy of agile development methodologies in delivering scalable and responsive business solutions, and they offer valuable insights for enterprises seeking to modernise their payroll systems in alignment with contemporary performance management paradigms.